Brexit and the decentred state. (January 2022) - Beech, Matt
The aim of this article is to examine Brexit through the lens of decentred theory. Decentred theory regards the British state as neither a monolith (as per modernist social science) nor a myth (as per post-modern theory) but rather as a repository of norms, customs, practices and thought acquired by elite actors, professionals and policy networks. The central thesis of the article is that the idea of the decentred state, as an explanation of state governance, can be seen in the phenomenon of Brexit. The article uses literatures on governance and contemporary history to examine the relevance of the concept of the decentred state. Then it considers the case study of British politics in the 1970s as a precursor to the decentring effects of Brexit on state governance. The article then moves to consider three dimensions of the phenomenon of Brexit which can be understood as decentring practices in and of themselves: the referendum vote, the negotiations and competing 'imaginings' of the United Kingdom in a post-European Union membership environment. The article's findings represent a fresh and novel means by which scholars can utilise the idea of the decentred state as an intellectual tool to explain the phenomenon of Brexit.